Breakthrough communities : sustainability and justice in the next American metropolis - Pavel, M. Paloma, 1951- (Urban and industrial environments. Sustainable metropolitan communities books., 2009)
Activists, analysts, and practitioners describe innovative strategies that promote healthy neighborhoods, fair housing, and accessible transportation throughout America's cities and suburbs.